Do leaf nitrogen resorption dynamics align with the slow‐fast continuum? A test at the intraspecific level. (7th March 2022) - Sartori, Kevin; Violle, Cyrille; Vile, Denis; Vasseur, François; de Villemereuil, Pierre; Bresson, Justine; Gillespie, Lauren; Fletcher, Leila Rose; Sack, Lawren; Kazakou, Elena
Abstract: The links between internal nitrogen recycling through the process of resorption from senescing leaves, whole‐plant resource‐use strategies and performance remain elusive. Indeed, tests of such potential linkages are hampered by the classical evaluation of plant nitrogen resorption efficiency (REN ) based on 'snapshots' of leaf nitrogen concentration from adult and senescent leaves. We significantly increased the resolution for measuring leaf nitrogen resorption by non‐destructively tracking time courses of nitrogen concentration in leaves of 137 natural Arabidopsis thaliana genotypes native to a wide range of climates across Europe, grown in a greenhouse. In addition to the classical measurement of resorption efficiency, we computed the relative maximum resorption rate of nitrogen (RRN ), that is, the amount of nitrogen remobilized by a leaf per unit time and per unit nitrogen, together with slow–fast syndrome traits at the leaf and whole‐plant levels. Across genotypes, high rates and efficiencies of nitrogen resorption were associated with low specific leaf area and late flowering. The RRN showed significant heritability, genetic associations and was negatively correlated with the mean annual temperature of the native populations. By contrast, despite the evidence of a correlation with temperature, REN showed lower heritability and no evidence of genetic association, questioning the mechanisms of nitrogen resorption. Overall, our results suggest a much stronger adaptive role for leaf nitrogen resorption than previously uncovered. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.